A Hemodialysis Patient With Secondary Hemochromatosis and Miliary Tuberculosis - Dogukan, Ayhan; Ozalp, Goksel; Ozercan, Ibrahim; Aygen, Bilge; Gunal, Ali Ihsan; Bahcecioglu, Ibrahim Halil (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2005)
While treatment with intravenous iron is essential for iron deficiency in hemodialysis patients, there is also evidence that links iron and iron overload with an increased risk of infection. In this article, we present a hemodialysis patient who develops secondary hemochromatosis and subsequent miliary tuberculosis.
Keywords: hemochromatosis; tuberculosis; hemodialysis